Cdc25A Protein Phosphatase: A Therapeutic Target for Liver Cancer Therapies - Wang, Z.; Kar, S.; Carr, B. I. (Anti-Cancer Agents in Medicinal Chemistry, 2008)
Cdc25A, a dual specificity protein phosphatase, is well-recognized as a critical regulator for cell cycle progression. We recently found that it also regulates mitogen-activated protein kinase (MAPK) signal transduction pathway. Inhibition of Cdc25A activity by a K vitamin analog Compound 5 (Cpd 5) can induce a strong and prolonged activation of epidermal growth factor receptor (EGFR)- MAPK pathway, which leads to suppression of transcription factors CREB and c-Myc, resulting in decreased expression of Cdc25A and cyclin D1 levels. Our investigations suggest that Cdc25A plays a central role in regulating and linking cell cycle progression and MAPK signal transduction pathways. Several other recently synthesized K vitamin analogs also affect this pathway, including the non-quinone PM20 and fluoro-Cpd 5. Thus, searching for new and efficient small molecules to inhibit Cdc25A activity may provide new means to control cancers of the liver and other sites.
Keywords: cell cycle